IDENTIFIKASI KEBERADAAN BAKTERI Aeromonas hydrophila PADA IKAN NILA (Oreochromis niloticus)YANG DIBUDIDAYAKAN DI KOLAM BALAI BENIH IKAN KARANGANYAR KABUPATEN PEKALONGAN - Esti Maret Rofiani; Benny Diah Madusari; Hayati Soeprapto (Fakultas Perikanan Universitas Pekalongan, 2017)
Nile tilapia (Oreochromis niloticus) is one of the freshwater commodities which has high economic value and has been farmed in many countries around the world, including Indonesia. One of the obstacles in the cultivation of nile tilapia is fish diseases. One type of fish diseases often suffered is a bacterial disease caused by Aeromonas hydrophila, which affects freswater fish species in tropical waters. This research aims to find indications of Aeromonas hydrophila bactery infection in nile tilapia gift (Oreochromis niloticus) and water quality measurement of the nile tilapia farming pond in Karanganyar Fish Breeding Center. This research was held on 27th Desember 2016 - 23th January 2017. The method used in this research is a sample survey methods and examination of test bacteria by conventional method, sampling is done on 3 ponds at Karanganyar Fish Breeding Center which each pond is taken three fish. Then, the samples were analyzed in Fish Quarantine Class II of Tanjung Mas, Semarang. The result showed that farmed nile tilapia gift in the fishpond in fish Breeding Center of Karanganyar has indicated 7.40% infected with the bacterium Aeromonas hydrophila, which 3,70% in the pond B, with the samples code B3.liver and 3,70% in the pond C, with the sample code C1.gill filament. The value of water quality parameter measured in the range of optimal for cultuation of fish. Keywords: Oreochromis niloticus, Aeromonas hydrophila, the fishpond in Fish Breeding Center of Karanganyar.